Limb loading enhances skill transfer between augmented and physical reality tasks during limb loss rehabilitation. - Hunt, Christopher L.; Sun, Yinghe.; Wang, Shipeng.; Shehata, Ahmed W.; Hebert, Jacqueline S.; Gonzalez-Fernandez, Marlis.; Kaliki, Rahul R.; Thakor, Nitish V. (Tufts University. Tisch Library., 2023)
Keywords: Upper-limb prostheses, Myoelectric control, Augmented reality, Proprioception.; Springer Open.